Dimensional relationship between maxillary sinuses, frontal sinusess, and craniofacial parameters using CT in Hospital Universiti Sains Malaysia - Otaifah, Abdullah Garallah Ali (2020)
The importance of paranasal sinuses cannot be denied as they have close relationships with vital organs such as the brain, eye, nose, and mouth. They grow deep within several facial skeletons and play many functions, such as increasing the voice resonance and acting as a crumpling zone in case of facial trauma skeletons. Nowadays, the advanced medical images database, such as the CT scan database facilitates the study of the paranasal sinuses and their relationships with other structures. Therefore, this study aimed to investigate the correlation between the maxillary and frontal sinuses dimensions and craniofacial parameters in CT scan and to identify the differences between gender in these structures. This was performed by using the head CT scan images, retrospectively analyzed from the database accessible in the Hospital Universiti Sains Malaysia. There were 120 subjects, which consisted of 60 males and 60 females. These subjects were divided into three groups; the first group with age between 5 to 10 years old, the second group, between 11 to 20 years old and the third group, between 21 till 40 years old. The measurements of maxillary sinus dimensions, frontal sinus dimensions and craniofacial parameters on the CT images were obtained by using computer software. The result of this study showed a statistically significant correlation between maxillary dimensions with all craniofacial parameters observed within the age of 5 to 10 years old. This correlation lasted till age 20 but became weak between age 21 till 40 years old. Also, there was a significant correlation between midfacial parameters with frontal sinuses dimensions. This correlation was more significant with the nasal structure. The correlation between maxillary and frontal sinuses dimensions was not significant. On the other hand, gender determination showed significant results towards the maxillary sinus, frontal sinus and midfacial structures. In conclusion, dimensional correlations exist between the maxillary and frontal sinuses with craniomaxillofacial parameters. These correlations constantly change with ageing. Also, this study showed significant variations between males and females in the maxillary sinus, frontal sinus and midfacial parameters.